PANDANGAN ISLAM DAN PANDANGAN SUKU SAMAWA TERHADAP PERNIKAHAN SESAMA JENIS - Nurfiya Syahrani; Nurul Yakin; Muhammad Fahrurrozi (FiTUA: Jurnal Studi Islam, 2022)
In recent years, the issue of same-sex marriage (gay and lesbian) is spreading on the surface and has been widely discussed by various groups. In Indonesia, the number of perpetrators of same-sex marriage is increasing in the name of human rights that must be respected and upheld, so this certainly raises pros and cons. This increase occurred due to increased internet access; the world of entertainment showing LGBT dramas; unrestricted access to pornography; narcotics; and the emergence of many LGBT movement organizations. In addition to biological factors, the influence of the immediate environment, namely family, relationships, and sexual violence, is also the cause of the emergence of LGBT. Same-sex marriage is prohibited in Islam because it violates nature and is contrary to Islamic Shari'a so that it triggers the maintenance of honor, soul, lineage, and reason. In short, same-sex marriage interferes with human physical and mental health. In the view of the Samawa tribe, same-sex marriage is also a deviant behavior, so that the perpetrator will be given punishment according to the existing customs and developed in the Samawa tribe.